Pensamento político moderno e fundamentos dos direitos humanos: perspectivas para o século XXI - Veiga, Marcelo (2007)
The present work aims to approach the concepts of human rights and dignity human being from the conception of modern politics. It presents a synthesis of the evolution of the modern thought as for the establishment of the concepts of individual, society and State, basic for the definition of the contours and limits of the human rights seen as universal. After that, exposes the debate concerning the tension produced for the positions that defend the universalism and the cultural relativism, in face of a paradox that demonstrates the affirmation of fundamental rights and, at the same time, its constant disrespect. As alternative for the overcoming of the tension and the paradox, it presents the contributions of Boaventura de Sousa Santos sociologist, who suggests the adoption of a new paradigm supported for the possibility of construction of an intercultural dialogue and for the concepts of emancipation politics and diatopic hermeneusm.